Urgensi Maqashid Al-Syariah Dalam Manajemen Perbankan Syariah - Zaki Zamani (Universitas Islam Lamongan, 2017)
Al-Quran and Hadith are a source of primary law which is to be reference of any decision on Islamic law. The determination of sharia law should be preceded by the unveiling on sharia destinations or secrets. The secret destination is called maqashid al-Shariah. It is important to make maqashid al-Shariah as a paradigm in the determination of the law, especially for issues that are not explicitly mentioned in the al-Quran and Hadith, especially in this modern era, which is human life experience a lot of progress in various fields. One of areas that have developed very rapidly is economics. Nowadays, a lot of new economic transactions emerge that has never existed in the previous era. The progress is very visible in the banking sector. The vital position of banking in the economy makes a lot of product innovation to meet the needs of the majority of people who depended on it, either directly or indirectly. One of the products which is resulted by the application of maqashid in the field of economics of banking is a tool called Maqashid al-Shariah Index (MSI). This measure is used to determine the performance of a company by using maqashid as a base of orientation. MSI may be an alternative in assessing the performance of a bank compared with measuring devices that have been there before, such as CAMEL, EVA, ROA, and ROE. In fact, MSI has advantages in considering the non-financial aspects, in fact, have a positive impact on the long-term financial performance. Keywords: Maqashid al-Sharia Index, Economic Matters